PENERAPAN METODE SUPPORT VECTOR MACHINE MENGGUNAKAN OPTIMASI GENETIC ALGORITHM UNTUK PREDIKSI PENYAKIT DIABETES - Frisma Handayanna (LPPM STMIK Antar Bangsa, 2015)
Abstract—Currently diabetes progressively increasing number of sufferers. Diabetesis a disease that can lead to complication scan even causedeath. Many studies using theme thod of Support Vector Machine predicting diabetes butthe accuracy ofthe resulting valueis stillless accurate. Inthis stud ycreate da mode lof Support Vector Machine algorithm toget the rulein predicting diabetes and provide a more accuratevalue of accuracy. After testing the model of Support Vector Machine and Support Vector Machine, the results obtained are thusobtained testing algorithm using Support Vector Machine where the value obtained accuracy is 74.21% and the AUC value is 0.758 and testing by using Support Vector Machine based Genetic Algorithm accuracy 75.26% values obtained with precision value 76.25 % and the AUC value is 0.771.